2016
DOI: 10.4137/sart.s33389
|View full text |Cite
|
Sign up to set email alerts
|

Are Smoking Cessation Treatments Associated with Suicidality Risk? An Overview

Abstract: Risk of suicidality during smoking cessation treatment is an important, but often overlooked, aspect of nicotine addiction research and treatment. We explore the relationship between smoking cessation interventions and suicidality and explore common treatments, their associated risks, and effectiveness in promoting smoking reduction and abstinence. Although active smokers have been reported to have twofold to threefold increased risk of suicidality when compared to nonsmokers,1–4 research regarding the safest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…In contrast, suicidality risks did not appear to show a significant increase associated with use of any specific smoking cessation pharmacotherapy. 39 Cigarette smoking itself is considered a predictor of suicidal acts. 35 , 40 Given these conflicting data, we considered that the evaluation of the suicidality risk for SCT is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, suicidality risks did not appear to show a significant increase associated with use of any specific smoking cessation pharmacotherapy. 39 Cigarette smoking itself is considered a predictor of suicidal acts. 35 , 40 Given these conflicting data, we considered that the evaluation of the suicidality risk for SCT is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…29 3). The numbers of cases were as follows: drug ineffective (143), wrong technique in product usage process (117), intentional drug misuse ( 52), incorrect dose administered (45), incorrect drug administration duration (40), expired product administered (39), drug administration error (35), and overdose (34). 4).…”
Section: Nrtmentioning
confidence: 99%
“…Suicide contributes to 1.4% of the global burden of disease, and the majority of cases belong to the age group of 15-35 years [4]. Several studies have demonstrated that nicotine or tobacco dependence is associated with suicide [5][6][7][8][9][10]. In addition, some epidemiological studies also reported a higher incidence of suicidal ideation among current but not former smokers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…CBT has been proven to help reduce cravings and promote smoking cessation by changing participants’ thoughts and behaviors [ 24 ]. The CBT quitting method consists of several parts, generally including preparation before quitting smoking, starting quitting smoking, and maintaining or preventing the recurrence treatment stage [ 25 ]. CBT may be a good choice for people who want to quit smoking, especially for those who want to quit smoking through nondrug methods [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CBT quitting method consists of several parts, generally including preparation before quitting smoking, starting quitting smoking, and maintaining or preventing the recurrence treatment stage [ 25 ]. CBT may be a good choice for people who want to quit smoking, especially for those who want to quit smoking through nondrug methods [ 25 , 26 ]. Our previous study on “Happy Quit” SMS text message smoking cessation in China found that a CBT-based smoking cessation intervention can effectively improve the 24-week continuous smoking cessation rate [ 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%